1985
DOI: 10.1002/ijc.2910350217
|View full text |Cite
|
Sign up to set email alerts
|

Induction of HLA class‐II antigen expression on human carcinoma cell lines by IFN‐gamma

Abstract: The effects of recombinant interferon gamma (IFN-gamma) on HLA antigen expression were examined in various human carcinoma cell lines: carcinomas of the lung (ChaGo, Oat 75, SK-LC-LL), colon (HT-29, WiDr), larynx (HEp-2), cervix (ME-180) and mammary gland (AlAb). Surface expression of HLA antigens was determined using monoclonal antibodies directed against monomorphic determinants of HLA class II (HD II, 2.06) and HLA class I (W6/32) by several techniques including indirect immunofluorescence, immunoperoxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…The peak fraction was used for the cellular radioimmuno assay (CRIA). The CRIA was performed in flexible polyvinyl chloride microtiter plates, as described previously (Schwartz et al, 1985). Plates were blocked for nonspecific binding by preincubation with PBS + 0.2% (v/v) In order to test for binding specificity of u-PA, representative cell lines of squamous cell carcinoma, large cell carcinoma, SCLC and mesothelioma were incubated with 2 x 106 c.p.m.…”
mentioning
confidence: 99%
“…The peak fraction was used for the cellular radioimmuno assay (CRIA). The CRIA was performed in flexible polyvinyl chloride microtiter plates, as described previously (Schwartz et al, 1985). Plates were blocked for nonspecific binding by preincubation with PBS + 0.2% (v/v) In order to test for binding specificity of u-PA, representative cell lines of squamous cell carcinoma, large cell carcinoma, SCLC and mesothelioma were incubated with 2 x 106 c.p.m.…”
mentioning
confidence: 99%
“…This indicates that HLA-DR antigens on adenoma and cancer cells may be related to local mononuclear cell infiltration, as well as to the neoplastic change of the epithelia. The association between HLA-DR antigens on cancer cells and infiltrated lymphocytes in the lesions was suggested from the fact that interferon gamma (Carrel et al 1985;Schwartz et al 1985), tumor necrosis factor (Pfizenmaier et al 1987), and other unknown agents produced by human lymphocytes (Groenewegen et al 1986) have the ability to induce expression of HLA-DR antigens on various human cell lines, including human colon cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, such as interferon gamma (Schwartz et al 1985) and tumor necrosis factor (Pfizenmaier et al 1987), that are released from lymphoid cells are known to induce HLA-DR antigens on the colonic cancer cells in vitro. Therefore, mononuclear cell infiltration, capable of releasing such cytokines in the lesion, may be related to the induction of HLA-DR antigens in the neoplastic cells.…”
mentioning
confidence: 99%
“…GarciaEspejo et al [20] suggested that the release of lymphokines by the host immune system could play a role in inducing the expression of HLA-DR, on previously negative cells. Indeed colon carcinoma cell lines can be induced to express HLA-DR upon exposure to interferon [22], which is known to up-regulate class I and class II. In colon cancer HLA-DR appeared mainly in poorly differ entiated tumors [23].…”
Section: Discussionmentioning
confidence: 99%